1983
DOI: 10.1038/305427a0
|View full text |Cite
|
Sign up to set email alerts
|

L1 mono- and polyclonal antibodies modify cell migration in early postnatal mouse cerebellum

Abstract: A major event of nervous system development is the migration of granule cell neurones, during the early postnatal development of the cerebellar cortex, from their germinating zone in the external granular layer to their final location in the internal granular layer. During migration, many granule cells are seen in direct cell-surface contact with processes of Bergmann glia, a subclass of astrocytes. In the neurological mutant mouse weaver, however, migration of granule cells is impaired, probably due to a defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
259
0
7

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 471 publications
(274 citation statements)
references
References 18 publications
8
259
0
7
Order By: Relevance
“…It has been reported that although N-CAM has five Ig-like domains, only the two most amino-terminal Ig-like domains are involved in the homophilic binding [30], that the migration of neurons in developing rat cerebellum is linked to the expression of another Ig superfamily of the cell adhesion molecule, Ng-CAM [31,32], and that in Drosophila, three molecules of the Ig superfamily, namely fasciclin II, fasciclin III, and neuroglican, are expressed not only during neurogenesis but also after the nervous system is completely established [33]. Thus, it may be that MPTP$ with three Ig-like domains are required for the migration of neurons or the synapse formation during neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…It has been reported that although N-CAM has five Ig-like domains, only the two most amino-terminal Ig-like domains are involved in the homophilic binding [30], that the migration of neurons in developing rat cerebellum is linked to the expression of another Ig superfamily of the cell adhesion molecule, Ng-CAM [31,32], and that in Drosophila, three molecules of the Ig superfamily, namely fasciclin II, fasciclin III, and neuroglican, are expressed not only during neurogenesis but also after the nervous system is completely established [33]. Thus, it may be that MPTP$ with three Ig-like domains are required for the migration of neurons or the synapse formation during neurogenesis.…”
Section: Resultsmentioning
confidence: 99%
“…Fab fragments of anti-Li rabbit antiserum were provided by Drs. Vance Lemmon (Fab-i) and Fritz Rathjen (Fab-2) (Lindner et al, 1983). mAb H28.123 was obtained from Immunotech (Marseille, France).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, features in common to both proteins include (a) their gross domain structural organization (Moos et al, 1988;Burgoon et al, 1991); (b) their appearance as a pattern of polypeptides probably originated by partial proteolytic cleavage of a single precursor molecule (Grumet et al, 1984;Wolffet al, 1987;Sadoul et al, 1988); (c) the occurrence of a phosphorylation site on the cytoplasmic domain (Grumet et al, 1984;Faissner et al, 1985;Sadoul et al, 1989); (d) the tissue expression patterns in most areas of the nervous system on which data are available for corresponding developmental stages (Rathjen and Schachner, 1984;Stalleup et al, 1985;Daniloff et al, 1986;but ef. Shiga et al, 1990, for an exception); and (e) involvement in biological functions, such as neuronal migration (Lindner et al, 1983;Hoffman et al, 1986), promotion of neurite outgrowth (Lagenaur and Lemmon, 1987;Lemmon et al, 1989;Chang et al, 1990;Kadmon et al, 1990), and fasciculation (Hoffman et al, 1986;Fischer et al, 1986;Rathjen et al, 1987a). The argumentation that L1 and Ng-CAM may not be species homologues but relatives derived main has a three-dimensional structure similar to that of the immunoglobulin fold of the C2 subcategory.…”
Section: Structural Features Of Ig/fniii-like Proteins Concentrated Omentioning
confidence: 99%